1985
DOI: 10.1002/ajh.2830200304
|View full text |Cite
|
Sign up to set email alerts
|

Granulopoiesis in patients with congenital neutropenia

Abstract: Granulopoiesis was investigated in five patients with congenital neutropenia (CN) (one Kostmann type, four benign forms). In semisolid agar culture, the marrow cells of all five patients produced normal numbers of CFU-c (colony-forming unit-culture). The size and classification of colonies were normal. In suspension culture in vitro with exogenous colony-stimulating factor (CSF) generated from omental-conditioned medium (OMCM), the myeloid precursors of all patients could proliferate and differentiate into nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The bone marrow almost invariably shows an arrest of granulocytic maturation at the promyelocytic or myelocytic stage. [1][2][3][4][5][6] Patients with severe congenital neutropenia have an increased susceptibility to acute myeloid leukemia. [7][8][9][10] An abnormal response of granulocytic progenitor cells to granulocyte colony-stimulating factor (G-CSF) may play a part in the pathogenesis of severe congenital neutropenia.…”
mentioning
confidence: 99%
“…The bone marrow almost invariably shows an arrest of granulocytic maturation at the promyelocytic or myelocytic stage. [1][2][3][4][5][6] Patients with severe congenital neutropenia have an increased susceptibility to acute myeloid leukemia. [7][8][9][10] An abnormal response of granulocytic progenitor cells to granulocyte colony-stimulating factor (G-CSF) may play a part in the pathogenesis of severe congenital neutropenia.…”
mentioning
confidence: 99%
“…S evere congenital neutropenia (SCN) 1 is a heterogeneous disease state characterized by a severe reduction in circulating neutrophils ( Ïœ 0.2 Ï« 10 9 /liter), and a maturation arrest of bone marrow progenitor cells at the promyelocyte/myeloid stage (1)(2)(3). Myeloid progenitor cells from SCN patients frequently show reduced responsiveness to G-CSF in vitro (4,5).…”
mentioning
confidence: 99%
“…In vitro studies with colony-stimulating activities (CSA) from various sources have demonstrated that a normal or near to normal number of myeloid progen itors capable of giving rise to colonies is present in a proportion of patients with both adult and childhood chronic neutropenia [2,5,6], In this study, we have in vestigated the colony-forming capacity of the bone marrow myeloid progenitors from 6 pediatric patients with chronic neutropenia. Recombinant granulocytemacrophage colony-stimulating factor (GM-CSF) or interleukin 3 (IL3) or the conditioned medium of the 5637 bladder carcinoma cell line were used as growth factors.…”
Section: Introductionmentioning
confidence: 95%